Phonon anomalies in HfN - Mishra, Poonam; Aynyas, Mahendra; Sanyal, Sankar P (Recent Research in Science and Technology, 2012)
The phonon dispersion curve are determined by model (BSM) for the crystals transition metal mono-nitride (HfN) and compared with the experimental phonons, which forms perhaps the best test for this purpose. The eight numbers of parameters of the model are determined by using the some set of input data. The results and degrees of agreement obtained in each case show clearly the superiority of the “charge-transfer mechanism” for representing the deformations of electron shells used in the BSM. The phonon dispersion curves and phonon density of states in HfN have been measured in high-symmetry directions Δ, Σ and Λ by breathing shell model (BSM). Anomalies in the dispersion of the acoustic branches and optical branches have been detected which are well described by experimental results.